The Role of Social Media as a Means of Political Literacy of Millennials in the 2019 Presidential Elections Process (A Case Study in Garut Regency) - Enjang Abdul Latif; Idrus Afandi; Cecep Darmawan (AIBPM Publisher, 2020)
This study discusses the problem of political literacy through social media in the 2019 presidential election in Garut regency, literacy is a very important process in supporting public political education, especially in the process that adapts to the current proliferation of digital media, the number of hoaxes and framing in social media is clear evidence of the loss of the essence of the democratic process itself, the author’s goals is to see the extent of the influence of social media on political literacy in determining the presidential election of 2019 in Garut district, and how the contribution and participation of millennial in its implementation, the result of this study are that social media influences the process of millennial generation political literacy, whereby they can judge information about politics based on arguments that are relevant to the media they read both books, through seminar forums, discussions in organizations and media information that has presented valid data validity. The implication is, to create a critical competent and political literacy society with argumentative discussions.